PENGARUH JALUR KABEL BAWAH LAUT TERHADAP EKOSISTEM PANTAI TANJUNG BEMBAN - Nurdiansyah, Robby (Riset Sains dan Teknologi Kelautan, 2022)
Submarine cables were first laid in the 1850s and were then only used for telegraphic communications. The Java-Sumatera-Kalimantan Cable System (JASUKA) is a 354-kilometer submarine communications cable that spans Java, Sumatra and Kalimantan. JASUKA is owned by PT Telekomunikasi Indonesia (Telkom). This cable is considered the best cable for telecommunications because it uses fiber optic technology. This allows for very fast data transmission through a thin glass fiber to a receiver at the other end of the cable. This fiberglass is wrapped with a layer of plastic and steel wire for protection. Underwater cables are usually the same width as a hose used for watering plants. The filaments that transmit light signals on the wire are also very thin, about the size of a human hair. The fibers are covered with several layers of insulation and protection. Cables routed close to shore use an additional layer of armor for added protection. Submarine cables are not completely underwater. Near the coast, the cables are buried in the seabed for protection. Laying a submarine cable system is the submarine cable system that runs through Tanjung Bemban, Batam City, Riau Islands. In the deep sea, the cable is laid directly on the seabed, requiring several surveys. One of them is a study of coastal ecosystems. This paper is prepared as an overview of the results of coastal ecosystem surveys conducted on three main ecosystems.